Hyperglycemia potentiates the effect of ionic calcium in photoreceptor ellipsoid zone disruption in diabetic retinopathy - Ankita; Stefanickova, Jana; Saxena, Sandeep; Nim, Dwividendra K; Ahmad, Kaleem; Mahdi, Abbas A; Kaur, Apjit; Bhasker, Shashi K; Valaskova, Jela; Kruzliak, Peter (International ophthalmology, 2019)
PURPOSE: To study the association of serum ionic calcium and glycated hemoglobin (HbA1c) with retinal photoreceptor ellipsoid zone (EZ) disruption in diabetic retinopathy (DR). METHODS: This is a tertiary care center-based observational cross-sectional study. Sixty-three consecutive cases, divided into 21 cases each with no diabetic retinopathy, non-proliferative diabetic retinopathy and proliferative diabetic retinopathy were included. Twenty-one healthy controls were also included. Ellipsoid zone disruption was assessed using spectral-domain optical coherence tomography. Serum ionic calcium and HbA1c were measured using standard protocol. Patient data from cases were divided into two groups according to their HbA1c levels: group 1 (HbA1c < 7, n = 26) and group 2 (HbA1c > 7, n = 37). Data were analyzed statistically. RESULTS: Mean ionic calcium levels in group 1 and group 2 were 1.131 ± 0.073 mmol/dL and 1.170 ± 0.070 mmol/dL, respectively. In group 1, 11 out of 26 had EZ disruption (42.3%). Similarly, in group 2, 29 out of 37 had EZ disruption (78.4%). On logistic regression analysis, as compared to group 1, ellipsoid zone disruption was found to be positively associated with serum ionic calcium (p = 0.01) in group 2 cases. CONCLUSION: Increased levels of serum ionic calcium are associated with increased EZ disruption in patients with HbA1c > 7 in DR.
Keywords: Cross-Sectional Studies; Analysis of Variance; hyperglykemie; Calcium; Male; glykovaný hemoglobin; vápník; Photoreceptor Cells, Vertebrate; Diabetic Retinopathy; Adult; fotoreceptory obratlovců; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; diabetická retinopatie; Hyperglycemia; lidé; ženské pohlaví; studie případů a kontrol; analýza rozptylu; Glycated Hemoglobin; Humans; průřezové studie; Female; lidé středního věku; Middle Aged